Incorporating agricultural by-products as functional ingredients in the food industry to improve the nutritional properties of food items and investigating consumer perceptions regarding acceptability. - Pillay, Kalle Veronica (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScFoodSc)--Stellenbosch University, 2022.